A rare cause of neonatal hypercalcemia: Neonatal severe primary hyperparathyroidism: A case report and review of the literature - Abdullayev, Tural (Int J Surg Case Rep, 2019)
INTRODUCTION: Neonatal severe primary hyperthyroidism is an extremely rare disorder that occurs in the first six months of life. Early recognition and prompt surgical intervention are of vital importance for survival and to avoid neurological sequel. Hypotonia, lethargy, respiratory distress, and growth and developmental delay occur in association with elevated serum parathormone levels and hypercalcemia (Gannon et al., 2014). Definitive therapy involves total parathyroidectomy. CASE PRESENTATION: We are presenting a patient with Neonatal severe primary hyperparathyroidism, who successfully underwent total parathyroidectomy. The patient had been followed up with medical therapy until he was seven months old, with no adequate clinical response to medical therapy. Parathormone levels rapidly declined following total parathyroidectomy, and the parathormone level fell to zero after removal of the ectopic tissue with a second surgery, and the patient was discharged with full recovery. DISCUSSION: Sestamibi scintigraphy might not always show an ectopic parathyroid gland. In such conditions, confirmation of parathyroid glands excised with total parathyroidectomy by frozen biopsy is not sufficient to terminate surgery. Intraoperative parathormone monitoring is particularly important at this point. Persistently elevated parathormone levels should suggest a remnant parathyroid tissue at the surgical site or an ectopic parathyroid gland that needs to be excised. CONCLUSION: Neonatal severe primary hyperparathyroidism is a life-threatening condition. Early surgery is life-saving in cases in whom medical therapy fails to control the disease.